Iodoarylation of Arylalkynes with Molecular Iodine in the Presence of Hypervalent Iodine Reagents - Md. Ataur Rahman; Tsugio Kitamura (Molecules, 2009)
Iodoarylation of arylacetylenes was performed using a simple reagent system composed of molecular iodine and [bis(benzoyloxy)iodo]benzene. Most arylacetylenes efficiently underwent the iodoarylation reaction with electron-rich arenes to give trans 1,1-diaryl-2-iodoethene adducts regio- and stereoselectively. As an exception, the iodoarylation of p-methoxyphenylacetylene resulted in a mixture of E- and Z-isomers of the corresponding product.